If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -3b = 0 Solving 4a + -3b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3b' to each side of the equation. 4a + -3b + 3b = 0 + 3b Combine like terms: -3b + 3b = 0 4a + 0 = 0 + 3b 4a = 0 + 3b Remove the zero: 4a = 3b Divide each side by '4'. a = 0.75b Simplifying a = 0.75b
| x-12=35 | | -3x^2+19x+14=0 | | 3y+6+55+10=180 | | x^2+10*x-25=0 | | 7x^2+36x=-5 | | 4x^2-10x-6=0 | | x^2+8=9 | | y=3(x-3) | | 5a+11+3a-7=-4 | | 4x+12=100 | | x^2-7x+1=9 | | 2x^2+15x+21=0 | | 14=2(2)+2x+4x | | 10=1x+3x+1x | | 14=2x+2x+4x | | 8x+4+5x+9=12x+4 | | 11+[8+(-4)]= | | 5a+4b=-28 | | 81w^2-100p^2= | | 3*-1+4= | | (7x+5y)+(-8x-9y)= | | 9y^4(4y^2-8y+6)= | | -13x=221 | | y^2-17y+72=0 | | y^2-15y+56=0 | | -3(z-4)= | | -3z-2z= | | x-7.9=-5.5 | | 9x-5=76 | | 8x+24=48 | | 6x+12=60 | | 0=-8y+21 |